PERSEPSI TEORI KONTRUKTIVISME DALAM KEMAMPUAN BERPIKIR SISWA PADA MATA PELAJARAN AGAMA ISLAM DI MADRASAH ALIYAH SWASTA YPRA BATANG KUIS - Masyitah Masyitah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
In principle, Islamic studies equip students to have a complete knowledge of Islamic law and be able to apply it in the form of worship to Allah. The purpose of this study is to find out how the theory of constructivism when applied to students in islamic religious learning. The research approach used in this study is a qualitative descriptive approach that describes and describes a finding in the field. The results showed that: 1) Whether or not student learning outcomes are good, can be determined from the learning process in the classroom. During the learning process, educational interaction activities between teachers and students with various learning models will lead students to understand the material presented by the teacher faster. 2) Constructive learning spurs students' enthusiasm in learning Islamic Religious Education. This can be seen from the involvement of students in the discussions carried out so that students are able to regularly express opinions in turn besides the moderator.